Fast Olfactory Threshold Determination Using an Ascending Limits Procedure - Sijben, Rik; Panzram, Claudia; Rodriguez-Raecke, Rea; Haarmeier, Thomas; Freiherr, Jessica (Chemosensory Perception, 2018)
The Sniffin' Sticks test battery is currently considered the best alternative for the measurement of olfactory threshold, discrimination and identification capabilities. These tests still suffer from limitations, however. Most noticeably, the olfactory threshold test is an intensive task which requires participants to smell a large number of olfactory stimuli. This proves especially problematic when measuring olfactory performance of elderly patients or screening research subjects, as sensory adaptation plays an important role in olfactory perception.In the current study, we have determined that the cause of this limitation lies with the test's single-staircase procedure (SSP). Consequentially, we have devised an alternative ascending limits procedure (ALP). We here compared data obtained using both procedures, following a within-subject design with 40 participants. Olfactory threshold scores as well as number of trials required to complete the two procedures were investigated.The results show that the ALP provides reliable and correct olfactory threshold ratings, as the values showed a good correlation with those obtained using the SSP and mean values did not differ significantly. Task duration, however, did show a highly significant difference, completing the SSP required participants to complete over 40% more trials compared to the ALP.The here presented methodological improvement can save time and, more importantly, reduce participants' cognitive and sensory strain, which is not only more comfortable, but also limits the influence of adaptation, making any measured data more reliable.Improving standard screening methods can directly enhance the reliability of any future study using this procedure.
Keywords: Sniffin' Sticks; TDI; Psychophysics; n-butanol; Threshold